Pengembangan Latihan Imagery Dan Self-Talk Untuk Meningkatkan Kemampuan Shooting Game Atlet Nusantara Petanque Club - Wahyu Perdana, Sinar; Rahayuni, Kurniati; Taufik, Taufik; Supriyatna, Supriyatna (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
This study aimed to develop imagery exercises to improve the shooting game skills of Nusantara Petanque Club athletes. This research and development use the Research and Development method with the modified ADDIE model. (1) needs analysis, (2) product design, and (3) expert validation tests carried out by three validators, namely psychologists, petanque coaching experts, and petanque trainer experts. A needs analysis was conducted through direct interviews with Nusantara Petanque Club trainers. From the needs analysis results, three mental exercise products are packaged in an audio podcast, including imagery relaxation, self-talk, and anxiety. After the product has been made, an expert validation test is carried out by three validators, namely (1) a psychologist, (2) a petanque coaching expert (3) a petanque trainer expert. The validation results for relaxation imagery podcast audio get 85.71%, self-talk audio podcast at 85.71%, and anxiety podcast audio get 85.71%. Then, we tested the product in groups of 5 athletes who were randomly selected based on ability. In the group test, the results for relaxation, self-talk, and anxiety podcasts were 92.13%. Based on the small group test, the audio podcast product is declared feasible and can be used.